Art and theatre for health in rural Cambodia. Issue 1 (1st January 2018) - Nguon, Chea; Dysoley, Lek; Davoeung, Chan; Sovann, Yok; Sanann, Nou; Sareth, Ma; Kunthea, Pich; Vuth, San; Sovann, Kem; Kol, Kayna; Heng, Chhouen; Sary, Rouen; et al.
ABSTRACT: This article describes our experience using art and theatre to engage rural communities in western Cambodia to understand malaria and support malaria control and elimination. The project was a pilot science–arts initiative to supplement existing engagement activities conducted by local authorities. In 2016, the project was conducted in 20 villages, involved 300 community members and was attended by more than 8000 people. Key health messages were to use insecticide-treated bed-nets and repellents, febrile people should attend village malaria workers, and to raise awareness about the risk of forest-acquired malaria. Building on the experience and lessons learnt in the year prior, the 2017 project which was conducted in 15 villages involved 600 community members and attracted more than 12, 000 people. In addition to the malaria theme, upon discussion with local health authorities, secondary theme (infant vaccination) was added to the 2017 project. We learnt the following lessons from our experience in Cambodia: involving local people including children from the beginning of the project and throughout the process is important; messages should be kept simple; it is necessary to take into consideration practical issues such as location and timing of the activities; and that the project should offer something unique to communities.